Analisis Item Soal Kimia SMA Menggunakan Rasch Model - Rina Ika Octaviana; Muhammad Burhan Anggara; Rayhan Jamilah; Ayi Darmana; Retno Dwi Suyanti (Chemistry Education Department of Education and Teaching Faculty, 2022)
Assessment is a technique for evaluating student learning outcomes and deciding whether or not the learning objectives have been achieved. This study aims to determine the validity, reliability, and difficulty level of the tested items. The data collection technique used a documentation technique in the form of an answer sheet for the odd semester final exam for the 2021/2022 academic year for class XI at SMAS Al-Amjad Medan with a total of 222 respondents, and the form of the question was 45 multiple-choice questions (dichotomies) with five categories of answers. The Rasch model is used to obtain fit items. This analysis was carried out with the help of Winsteps software version 3.7.3. Based on the results of the analysis of the results of the item analysis using the Rasch model, the following conclusions can be drawn: in terms of validity, the questions consist of 86,67% valid and 13,33% invalid; Cronbach's alpha value of 0,95 in the very good category, the Person Reliability value is 0,93, which is included in the excellent category; the Item Reliability value is 0,95 in the special category; the distribution of the difficulty level of the item items is by the rules for making questions because 8 items (17,78%) are in the very difficult category, 9 items are about (20%) are in the difficult category, 23 items are about (51,11%) are in the easy category and 5 items (11,11%) in the very easy category.